Kajian Tindak Tutur Performatis Dalam Perspektif Epistimologi - Indah Arvianti (Universitas Aki, 2014)
Epistemology is a systemic science as a branch of philosophy about the origin of the science, the means, the method or the way to get it, the validity, and the truth of the science. When we say a word, there is an understanding between speaker and hearer that can be analyzed by ratio, sense, and experience. Both speaker and listener respond one to each other by those means in communication. Speech act analysis as a branch of pragmatics deals with the textual meaning. Before the speaker says speech act, he/she must concern the ratio, sense, and experience to produce a speech that must be understood by his/her partner. On the other hand, the listener also uses all those means to interpret the speech. By using those means both interlocutors share the same knowledge and method to get the understanding, so the communication may run well. Key words : epistemology, pragmatics, performative speech act